Kepentingan Bhutan Dalam Pembukaan Hubungan Diplomatik Dengan Israel Tahun 2020 - Harisa, Niswatul; Purwono, Andi (Kajian Hubungan Internasional, 2023)
This thesis aims to find out the reasons that prompted Bhutan to open diplomatic relations with Israel in 2020. This study was written using a qualitative approach, namely a study that uses data obtained through library research techniques such as books, official state documents, news and other mass media. This study uses the theory of national interest to determine the goals and interests of Bhutan. In this study, two reasons were found that pushed Bhutan to open diplomatic relations with Israel in 2020, namely the existence of Bhutan's national interests in the economic and military security fields.